2021
DOI: 10.1002/acm2.13454
|View full text |Cite
|
Sign up to set email alerts
|

SBRT of ventricular tachycardia using 4pi optimized trajectories

Abstract: To investigate the possible advantages of using 4pi-optimized arc trajectories in stereotactic body radiation therapy of ventricular tachycardia (VT-SBRT) to minimize exposure of healthy tissues. Methods and materials: Thorax computed tomography (CT) data for 15 patients were used for contouring organs at risk (OARs) and defining realistic planning target volumes (PTVs). A conventional trajectory plan, defined as two full coplanar arcs was compared to an optimized-trajectory plan provided by a 4pi algorithm th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…18 This F I G U R E 9 Comparison between measured dose (thin lines) and calculated dose (thick line) for the colli-DTRT plan of case 1 (top) and the NC-VMAT of case 6 (bottom). approach was also used for a planning study of ventricular tachycardia, 17 showing applicability in the thorax. For lung cases, the authors introduced a sampling score to maintain conformity 33 ; with dosimetrically motivated BAO as in our study, this was not needed.…”
Section: F I G U R Ementioning
confidence: 99%
See 2 more Smart Citations
“…18 This F I G U R E 9 Comparison between measured dose (thin lines) and calculated dose (thick line) for the colli-DTRT plan of case 1 (top) and the NC-VMAT of case 6 (bottom). approach was also used for a planning study of ventricular tachycardia, 17 showing applicability in the thorax. For lung cases, the authors introduced a sampling score to maintain conformity 33 ; with dosimetrically motivated BAO as in our study, this was not needed.…”
Section: F I G U R Ementioning
confidence: 99%
“…4 MacDonald et al have automatically determined table angles and gantry-angle range for non-coplanar partial arcs with optimized collimator angle using overlap metrics to solve the BAO problem. 3 By considering partial arcs, the technique is more easily applicable to treatment sites in the body 17 where collision risk strongly limits the range of usable table angles for a full gantry rotation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work in the area of 4π radiotherapy has demonstrated the potential benefits of dynamic trajectories in radiotherapy (treatment deliveries in which the couch, gantry and collimator engage in continuous motion while the beam is on). The benefits include both a reduction in normal tissue doses and an increase in monitor unit efficiency 25–30 . In one clinical trial with 4π‐radiotherapy, treatment‐time tolerability for N = 11 cases was found to be tolerable (8.625 ± 2.64 out of 10) and was found to not cause nausea 31 .…”
Section: Introductionmentioning
confidence: 99%
“…The benefits include both a reduction in normal tissue doses and an increase in monitor unit efficiency. [25][26][27][28][29][30] In one clinical trial with 4𝜋-radiotherapy, treatment-time tolerability for N = 11 cases was found to be tolerable (8.625 ± 2.64 out of 10) and was found to not cause nausea. 31 To date, most of this research has focused on treatments delivered at the nominal isocenter of the treatment unit (i.e., conventional source-to-axis distance [SAD] treatments); however, the same capabilities that permit intra-treatment rotations of the couch also permit dynamic translations of the couch for the purpose of reducing the source-to-target distance.…”
Section: Introductionmentioning
confidence: 99%